2018
DOI: 10.1002/admt.201800436
|View full text |Cite
|
Sign up to set email alerts
|

3D Nanostructured Multielectrode Arrays: Fabrication, Electrochemical Characterization, and Evaluation of Cell–Electrode Adhesion

Abstract: Abstract3D nanostructures on top of planar multielectrode array (MEA) electrodes increase the surface area and can offer a tight and stable cell–electrode interface, thus leading to a crucial increase of the signal‐to‐noise ratio during measurement. However, each individual cell type might need specific dimensions and an arrangement of nanostructures that fits ideally to a specific cell type. Therefore, a fabrication method of 3D nanostructured MEA chips based on nanoimprint lithography, gold electroplating, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“… Susloparova et al (2015) created new substrates for ECIS using open gate field-effect transistors instead of gold electrodes, which allowed to obtain single-cell resolution of the impedance measurements. Decker et al (2019) employed 3D nanostructured multielectrode arrays to study cell adhesion. Using nanoimprint lithography, the authors created an electrode with incorporated nanostructures in different forms, dimensions, or pitch lengths in a reproducible way.…”
Section: Biological Applications Of Biosensorsmentioning
confidence: 99%
“… Susloparova et al (2015) created new substrates for ECIS using open gate field-effect transistors instead of gold electrodes, which allowed to obtain single-cell resolution of the impedance measurements. Decker et al (2019) employed 3D nanostructured multielectrode arrays to study cell adhesion. Using nanoimprint lithography, the authors created an electrode with incorporated nanostructures in different forms, dimensions, or pitch lengths in a reproducible way.…”
Section: Biological Applications Of Biosensorsmentioning
confidence: 99%
“…Apart from excellent resolution, another great feature of NIL is its reproducibility in fabrication of structures of different shapes, all organized in predefined structural geometry, dimensions and intra-structural distances. [26] In order to fabricate random nanostructures with NIL, the master stamp must have a random topographical pattern. The latter can be either achieved by designing a random pattern with computer algorithm and then developing it with engineering methods (e.g., e-beam lithography) or can be inspired from natural surfaces (e.g., nanostructure pattern on cicada moth wing).…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, nanostructuring techniques have been in use to generate metal nanostructures with spatial resolution as small as 100 nm for bioanalytical applications. [ 23–26 ] Furthermore, electrophysiological studies with neuronal cultures have shown significant improvement in cell–surface coupling and in bioelectrical signal transduction induced by these nanostructures. [ 23–26 ] Although most of the traditional nanostructuring techniques result in fabrication of regularly organized structures, the natural substrates in living systems on which cells attach and grow have a rough and irregular surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations